Human security in South Asia concept, environment and development - Subramanyam Raju, A. (Abingdon, Oxon ; New York, NY Routledge, 2020)
"This book delves into the theory and praxis of human security in South Asia. Home to almost a quarter of the world's population and fast emerging markets, South Asia holds social, geo-political, and economic significance in the current global context. The essays in the volume: examine the challenges to human security through an exploration of environmental issues including water availability, electric waste, environmental governance, and climate change; explore key themes such as development, displacement and migration, the role of civil society, sustainable development, and poverty discuss developmental issues in South Asia and provides a holistic picture of non-military security issues. Bringing together scholars from varied disciplines, this comprehensive volume will be useful for researchers, teachers and students of international relations, human rights, political science, development studies, human geography and demography, defence and strategic studies, migration and diaspora studies, and South Asian studies"--
Human security : a conceptual framework / Adluri Subramanyam Raju -- Measurements of human security : a conceptual analysis / Swaran Singh and Archana R. -- Human security and beyond / Santishree D. Pandit -- Human security in South Asia : the locus of a cooperative context / I.P. Khosla -- Is the region ready? Can the state deliver? Essay from India / D. Suba Chandran -- Is the region ready? Can the state deliver? Essay from Pakistan / Salma Malik -- Water insecurity in South Asia : challenges of human development / Vandana Asthana -- Climate change and human security : a case study of Maldives / Rabindra Sen -- Dangers of electronic waste in India : a concern for human security / Gopalji Malviya -- Correcting anomalies of a dysfunctional state through civil society : initiatives to complement global attempts for human security / C.K. Lal -- Human development vis-a-vis gross national happiness in Bhutan : challenges and achievements / Maitreyee Choudhury -- Linkages between migration and poverty in Nepal / Amrita Limbu -- Sustainable development model : experience from India / Rashmi Bhure -- Reintegrating India's Maoists : surrender and rehabilitation / P.V. Ramana -- Development induced displacement : case studies from India / Apoorva R. Heroor and Praveen Tiwari.
Includes bibliographical references and index.
Keywords: Economic development -- South Asia; Human security -- South Asia; Quality of life -- South Asia; South Asia -- Economic conditions; South Asia -- Environmental conditions; South Asia -- Social conditions